Pengaruh preferensi sumber pembiayaan dan tingkat pendidikan terhadap pendapatan usaha mikro dan kecil di Indonesia - Ramel Yanuarta RE; Indah Krismanola (Jurnal Kajian Manajemen dan Wirausaha, 2021)
This research aims to analyze the effect of financing preference and the level of education of entrepreneurs on quintile of Micro and Small Enterprises (MSEs) revenue in Indonesia. The data used in this research is IFLS data (Indonesian Family Life Survey) waves 4 and 5 with a total sample of 10,336 business units that meet the criteria. Considering the heterogeneous characteristics of the data and the presence of outliers, this study used quantile regression method with a level of confidence (∝=0.05). The results of the analysis show that the education level of entrepreneurs has a positive effect on MSEs revenue and the effect is stronger on the higher MSEs revenue quantile. Meanwhile, the financing preference from own capital generates lower income compared to external or combined sources of financing and the difference is greater in the higher MSEs revenue quintile.